Physiological aid for children with osteogenesis imperfecta - Pashenko, Andrey; Yatsenko, Tatyana; Khmyzov, Sergey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
Last decade there is growth of interest to the problem of children with combined physiological disorders and musculoskeletal system, like osteogenesis imperfecta (OI). Objective: to assess the complex physiological aid to patients with OI aged 4 months to 60 years and its influence on the treatment efficacy. Methods: we examined 40 patients with OI aged 4 months to 60 years old. We used Thomas questionaries, tests projects «Non existing animal», Lusher colored test, Kettells test. Diagnosis of interpersonal relations was carried out according to T. Leary’s methodology. Studied the opinion of the subject about himself and the idea of what others see it (Q-sorting). For the study of quality of life (QL) a questionnaire was created according to the tasks of the orthopedic and traumatological clinic and the index of QL (IQL) was calculated. Results: patients with OI belong to the risk group of development of psychopathological manifestations, neurotic disorders due to the relaxation of the barrier of psychological adaptation. Their IQL was (–5.6 ± 0.3) scores, it indicated a low social status. Mental tension on the eve of surgery and in the first week of treatment is indicated by all patients. This is a consequence of the stress-reaction with all its characteristic components: braking in the cortex, excitation in the subcortical formations, dysfunction of the endocrine glands, and changes in homeostasis at all levels. Depression is a general reaction of the body to the long-term effects of severe chronic stress. A psychological correction course of 10 exercises has been developed, which includes muscle relaxation, visualkinesthetic dissociation, techniques of positive imagination. After the course of psychocorrection, patients noted improvement in emotional state, reduction or disappearance of anxiety symptoms, significant improvement in psychological status and QL. Conclusions: comprehensive psychological support and psychocorrection of patients with OI contribute to improved treatment outcomes and, consequently, better positive motivation and full socialization.